The Effects of Lateral Meniscus Posterior Root Tear and its Repair on Knee Stability of Internal Rotation and Forward Shift: A Biomechanical Kinematics Cadaver Study - Qi, Yan-Song; Bao, Hu-Ri-Cha; Tao, Li-Yuan; Gu, Pei-Liang; Kong, Chao-Le-Men; Wang, Jun-Chen; Xu, Yong-Sheng (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Lateral meniscal posterior root (LMPR) is an important stabilizer for knee joint, providing the stability during tibia forward shifting and internal rotating. It is still controversial that whether the LMPR tear (LMPRT) should be repaired together with ACL reconstruction. This study aims to investigate the effects of LMPR on knee stability with intact ACL. Methods: Eight cadaver knees were used and performed the biomechanical kinematics tests in orders of: Group A: the LMPR was intact; Group B: the LMPR was cut off from its tibial end; Group C: the LMPRT has been repaired. 1) An internal rotation moment (5 Nm) was given to the tibia, then the internal rotation angle of the tibia was measured; 2) An forward shifting force (134 N) was given to the tibia, then the anterior displacement of the tibia was measured; 3) An internal rotation moment (5 Nm) and a valgus moment (10 Nm) were given to the tibia, then the internal rotation angle and the anterior displacement was measured. The stability was inferred from smaller rotation angle and displacement, and all of the angles and displacements were measured at knee flexion of 0°, 30°, 60° and 90°, respectively. Results: Comparing to Group A, the internal rotation angle in Group B was increased significantly at knee flexion of 30° (p = 0.025), 60° (p = 0.041), 90° (p = 0.002); the anterior tibia displacement in Group B was increased significantly at knee flexion of 30° (p = 0.015), 60° (p = 0.024); at knee valgus, the internal rotation angle was also increased significantly at knee flexion of 60° (p = 0.011), 90° (p = 0.037). Comparing to Group B, the internal rotation angle in Group C was decreased significantly at knee flexion of 30° (p = 0.030), 60° (p = 0.019), 90° (p = 0.021); the anterior displacement in Group C was decreased significantly at knee flexion of 30° (p = 0.042), 60° (p = 0.037); at valgus, the internal rotation angle was also decreased significantly at knee flexion of 60° (p = 0.013), 90° (p = 0.045). Comparing to Group A, only the internal rotation angle (p = 0.047) and anterior displacement (p = 0.033) in Group C were increased at knee flexion of 30°. Conclusion: In simulated knee with intact ACL, LMPRT can still lead to the notable internal rotational instability at knee flexion from 30° to 90°, as well as the anterior shift instability at knee flexion from 30° to 60°. LMPRT repair help to improve the internal rotation stability at 30° and restore it at 60° to 90°, and improve the anterior shift stability at 30° and restore it at 60°.